Low temperature synthesis of carbon fibres and metal-filling carbon nanoparticles with laser irradiation into near-critical benzene1. Issue 17 (27th February 2015) - Fukuda, Takahiro; Hayasaki, Yasuhiro; Hasumura, Takashi; Katsube, Yoshihiro; Whitby, Raymond L. D.; Maekawa, Toru
<x xml:space="preserve">Abstract</x> A low temperature methodology for synthesising carbon nanostructures was developed utilising near-critical benzene.